Transformation of Berber Traditional Planning and Living Spaces - ASMAA SAADA; DJAMEL DEKOUMI (Journal of Contemporary Urban Affairs, 2019)
The Algerian Berber region was animated by a network of human settlements built according to the urban model of the Islamic medina and its traditional habitat of adobe. Various rural and urban development and transformation of planning and living spaces have recently come under the pressure of rapid urban growth. This study aims to analyze and compare Berber domestic spaces across a sample of houses from Aures valley, this region of Algeria which presents distinctive geological, geographical and historical characteristics. The study will look, first at the houses, then at similarities and differences in space configuration in order to pose questions of how this traditional architecture with its climatic and cultural solutions could be utilized or transplanted in the new urban context. The study focuses particularly on observing and analyzing different factors which influence urban life like social patterns, family lifestyle, a migration which may have led to some modifications in the social structure. This study attempts to learn how the traditional Berber built environment may be considered as a good example of an end product of an interaction between constant elements such as the religious factors, the climate, the landscape and changeable elements such as economic, technological and industrial means, that is to say, a product of a societal process.